Development of Pedagogical Competence Scale for Lecturers in Universities Using Item Response Theory - Olagunju, Barakat Adeoti; Iwintolu, Rukayat Oyebola (Universitas Pendidikan Indonesia, 2023)
To ascertain whether lecturers had the pedagogical competency skill needed in impacting students with necessary skills they need outside school, this study developed a scale to measure Lecturers’ Pedagogical Competence (LPCS) in universities using item response theory. The pedagogical competence of university lecturers was assessed using a set of items designed and evaluated the scale's construct validity. The initial scale consisted of a 70-item four options Likert-type. The multi-stage sampling procedure was employed. Proportional sampling was used to choose four universities in South Western Nigeria. At each of the institutions selected, 20% of the staff population was selected from all faculties using stratified random sampling with a cadre as a stratum. Thus, 906 lecturers from federal universities and 294 were selected from federal state universities, respectively. In all, 1,086 of the 1200 lecturers selected completed the study's instrument. The results showed that four of the six optimal factors underlying lecturers’ pedagogical competence were reliable. Eventually, 20 can measure LPC. Furthermore, the LPCS showed validity by optimally measuring the theoretical construct underlying the scale. Evaluation of learning outcome; managing student behavior during lecture; using ICT to Enhance learning; and lecturers’ student interaction remains the most important factors in LPCS.